BINA-DAMAI DALAM KOMUNITAS PESANTREN: SEBUAH UPAYA COUNTER-RADIKALISME - Rahman Mantu (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
This article discussed about the experience of al-Qodir Boarding School in Sleman Yogyakarta in the effort to counter the radicalism through the approach of peace building. Applying qualitative approach, this research using the methods of observation and deep interview in collecting data. With the theoritical framework of cognitive peace building, three factors of peace building became the focus; the mechanism of internal group, among group and external group. The main research finding here was the essential role of kiai in building participative dialogue with the community out of the boarding school which was implemented through social actions. It resulted in the ability of al-Qodir Boarding School in formulating the strategy of radicalism counter which became a typical strategy of pesantren among so many strategies to find out new formulations in avoiding the movement of radicalism in Indonesia.